跳躍眼球運動時の視野安定機構 - 後藤, 敏行; 池田, 光男 (Kogaku (Japanese journal of optics), 1981)
To investigate the mechanism of the saccadic stability of the visual system, the probability of perceiving the motion of the test stimulus was measured when the test and inducing stimuli shifted independently during a saccadic eye-movement. When the probability was plotted against the shift size of the inducing stimulus for a constant shift size of the test stimulus as parameter, the probability curves showed the dependence on the shift size of the inducing stimulus and took a minimum value where the test stimulus and the inducing stimulus had the same shift size and direction. Further, the curves were raised when the shift size of the test stimulus was increased. Those results indicate subjects perceived the test stimulus motion not only for the absolute shift of the test stimulus but also for the relative shift between the two. On the assumption that the probability of perceiving the test stimulus motion was a function of only the sum of the absolute shift of the test stimulus and the relative shift between both stjmuli, the theoretical probability curves were obtained, which explained the present results nicely. It was concluded that both the extra-retinal signal and the retinal signal were utilized for the process underlying the saccadic stability.